Additional Pertalite Policy and Gasoline Consumption Patterns in Indonesia - Nur Laila Widyastuti (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
The transport sector is the largest contributor to CO2 emissions in Indonesia. To reduce the emissions, a policy of adding pertalite is applied which aims to allow consumers to switch into higher quality gasoline. This paper examines the impact of the implementation of the policy of adding pertalite. The approach uses the fixed effect of the panel data estimation method. In the period 2010-2015 Pertamax prices have a negative impact on Pertamax and Premium consumption. Meanwhile, the prices and revenues of selling Premium have a positive impact on consumption of Pertamax and Premium. For the period of 2016, the impact of the Pertamax prices increase would be a decrease in Pertamax and Premium consumption. Changes in the pattern of gasoline consumption are possible because of the difference in price and supply constraints for each type of gasoline. Therefore, the government should control the supply of gasoline and the differences in gasoline prices so that more Premium consumers will switch to Pertalite, and Pertalite consumers will switch to Pertamax.